Characterization of ESBL (SHV-12) producing clinical isolate of Enterobacter aerogenes from a tertiary care hospital in Nigeria - Budak Fatma; Kolayli Fetiye; Torol Sinem; Fashae Kayode; Kasap Murat; Vahaboglu Haluk (BMC, 2010)
Abstract Background We studied the beta-lactamases of an E. aerogenes isolate recovered from the blood of a two-year-old patient. The isolate demonstrated a disk-diffusion phenotype typical for an AmpC-ESBL co-producer. Methods Microbiology studies were performed according to standard protocols. The resistance gene was identified by transconjugation and cloning experiments. Results By transconjugation only a narrow spectrum beta-lactamase (TEM-1) encoded on a small plasmid was transmitted. The ESBL was cloned and expressed in an E. coli host. Sequence analysis of the recombinant plasmid revealed blaSHV-12 associated to the insertion sequence, IS26. Conclusion This is the first study demonstrated the occurrence of SHV-12 in Nigeria.